The Impact And Challenges Of Task-Based Language Teaching (TBLT) In Developing Communicative Competence Within EFL And ESP Contexts - Abdulkhakimova, Mohlaroy (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
Abstract This article analyzes the effectiveness of Task-Based Language Teaching (TBLT) in developing the speaking competence of English as a Foreign Language (EFL) and English for Specific Purposes (ESP) learners. Drawing on data from diverse academic settings in Uzbekistan, Pakistan, and Iraq, the study examines the impact of meaning-focused tasks on speaking fluency, accuracy, and student motivation. The findings indicate that TBLT significantly enhances learners’ communicative abilities, although it requires additional pedagogical interventions to improve grammatical accuracy and pronunciation. The article also addresses challenges such as teacher professional development and curricular constraints.